(untitled) (Global Journal of Human-Social Science, 2024)
For over two decades in France the concept of bi entraitance has echoed within the walls of nursing homes While recommendations for good professional practices stand as a beacon for the care of the elderly aiming to prevent the indignity of mistreatment they may not consistently guide daily care giving practices in these establishments This study does not delve into the reasons for this discrepancy Instead it presents three situations extracted from the field exploring the concepts of bi entraitance and its antithesis Employing a qualitative and reflective approach the research seeks to examine the nuanced boundary between these two antagonistic modes of care The caregiver s individual response becomes pivotal signifying their positioning whether to remain or contemplate a shift while respecting the construction of their professional identity and the dignity of the vulnerable individual This study aligns with a broader perspective on accompaniment and care in gerontology conceptualizing it as an ethics in itself Beyond a mere exploration of practices it endeavors to contribute to a profound understanding of care giving dynamics urging practitioners to contemplate their actions in the context of an ethical commitment to the wellbeing and dignity of those in their care